Study Effect of Plant Extraction for Quercus infectoria on Some Species of Bacteria - Breesam, Basim Kadhim; Abdullah, Jasim A. (Scientific Journal of Medical Research, 2020)
Objectives: This study focused on observing the effectiveness of the inhibitory effect of two types of treatments on bacterial growth in three types of bacteria, as Amoxicillin was used as a treatment and oak (peat) Quercus infectoria (bark) in a plant extract form so that we observe the inhibitory effect of these substances on the growth of bacteria. Methods: The current study included Quercus infectoria (bark) oak as extract and Amoxicillin as a treatment and three bacterial types: Staphylococcus aureus, Escherichia coli, Klebsiella pneumonia and this study was conducted to note the inhibitory effect of peat extract and amoxicillin on growth. Results: Through this study, we observed that the inhibitory action of peat plant extract was better than Amoxicillin on Staphylococcus aureus, Escherichia coli, Klebsiella pneumonia, while Amoxicillin had no significance effect on the Escherichia coli, Klebsiella pneumonia for all concentration as noted that at best Concentration of 0.12 mg /ml of peat extract when compared with amoxicillin treatment. Conclusion: No significant difference was observed between the concentrations of the plant extract and its effect on bacteria, as it was noted that the extract plant had a highly effect on both types of positive and negative bacteria of Gram stain and better than amoxicillin treatment.